Antibacterial coating with TaCu nano multilayer structure and preparation method thereof
Through the antibacterial coating of TaCu nano-multilayer structure, the problem of insufficient antibacterial performance of bone implant materials is solved, long-term antibacterial and osteogenic activity is achieved, and the process is simple and efficient, and it meets biosafety standards.
Patent Information
- Application Number
- CN202410071740.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-18
- Publication Date
- 2024-12-20
AI Technical Summary
Existing bone implant materials have shortcomings in antibacterial properties and biocompatibility, especially the long-term antibacterial ability of single-layer composite coatings is weak, and doping antibacterial agents into the material is expensive and complex in operation, which is easy to cause Inflammation.
The antibacterial coating with TaCu nano-multilayer structure is used to alternately stack the Cu layer and Ta layer. The Cu layer is the outermost layer. The magnetron sputtering technology is used to form a coating with excellent antibacterial properties on the substrate, and the Ta layer is the most The outer layer is used to enhance osteogenic properties.
It achieves long-term antibacterial properties, reduces cytotoxicity, promotes osteocyte proliferation, and has a simple process, fast deposition speed, high binding strength, and meets biosafety material standards.
Smart Images

Figure CN119158077A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biological coatings, and in particular to an antibacterial coating with a TaCu nano multilayer structure and a preparation method thereof. Background Art
[0002] In the field of orthopedics, ideal bone implant matrix materials need to have multiple properties: excellent mechanical properties, the ability to effectively reduce bacterial adhesion, strong antibacterial properties, good biocompatibility, and a certain degree of bone integration. However, the method of doping antibacterial agents inside the material is costly and complicated to operate, and the requirements for bone implant performance are more stringent; the method of implant injection is prone to local surges of antibacterial agents, causing inflammation around the implant. In contrast, it is simpler and more efficient to apply a nano-coating containing antibacterial substances to the surface of a bone implant. It does not require too much pre-treatment of the bone implant, can directly contact bacteria and release antibacterial substances, while reducing costs, effectively reducing bacterial adhesion and avoiding the formation of biofilms.
[0003] With the continuous advancement of medical technology, a feasible method to improve the osteogenic performance of materials is to perform osteogenic modification on the surface of the matrix material and carry nanoparticles with osteointegration properties. In recent years, tantalum coatings with their excellent osteogenic properties are believed to be applied to the surface of bone implant materials to promote osteointegration. Carrying tantalum coatings on titanium substrates not only helps cell adhesion, but also combines the good biocompatibility of titanium materials and the excellent osteogenic properties of tantalum materials, playing a key role in the generation, proliferation, differentiation and mineralization of bone cells.
[0004] The Chinese patent with publication number CN112458395A discloses a method of preparing a Ta-Cu-Zn composite coating using a titanium alloy as a substrate by plasma spraying technology. However, the long-term antibacterial ability of a single-layer composite coating is generally weak. Summary of the invention
[0005] In view of this, the object of the present invention is to provide an antibacterial coating with a TaCu nano multilayer structure and a preparation method thereof. The antibacterial coating provided by the present invention has excellent antibacterial properties, especially long-term antibacterial properties.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The invention provides an antibacterial coating with a TaCu nano multilayer structure, comprising a Cu layer and a Ta layer which are alternately stacked on a substrate in sequence, wherein the Cu layer is in contact with the substrate, and the Ta layer is the outermost layer.
[0008] Preferably, the number of Cu layers and Ta layers is independently ≥5 layers.
[0009] The present invention also provides a method for preparing the antibacterial coating having a TaCu nano multilayer structure as described in the above technical solution, comprising the following steps:
[0010] Pretreating the substrate to obtain a pretreated substrate;
[0011] The Cu layer and the Ta layer are alternately magnetron sputtered on the pretreated substrate in sequence to obtain the antibacterial coating with the TaCu nano multilayer structure.
[0012] Preferably, the parameters for alternately magnetron sputtering the Cu layer and the Ta layer on the pretreated substrate include: the protective atmosphere is argon, the working gas pressure is 0.5-0.75 Pa, the Cu target is RF magnetron sputtering, the RF magnetron sputtering power is 38-42 W, the Ta target is DC magnetron sputtering, the DC magnetron sputtering power is 98-102 W, and the alternating deposition of the Cu layer and the Ta layer is achieved by controlling the revolution position of the substrate fixing table.
[0013] Preferably, the single magnetron sputtering time ratio of the Cu target to the Ta target is 1 to 5:10.
[0014] Preferably, the parameters for alternately magnetron sputtering the Cu layer and the Ta layer on the pretreated substrate further include: the rotation speed of the substrate fixing table is 3.8-8 r / s.
[0015] Preferably, the parameters for alternately magnetron sputtering the Cu layer and the Ta layer on the pretreated substrate further include: a target-substrate distance of 5 to 6 cm.
[0016] Preferably, the flow rate of the argon gas is 30-35 sccm.
[0017] Preferably, the pretreatment comprises sequentially performing acetone ultrasonic washing and ethanol ultrasonic washing;
[0018] The power of the acetone ultrasonic washing is 90-100W, and the time is 25-30min;
[0019] The power of the ethanol ultrasonic washing is 90-100W, and the time is 25-30 minutes.
[0020] Preferably, the substrate is TC4 titanium alloy.
[0021] The present invention provides an antibacterial coating with a TaCu nano multilayer structure, comprising a Cu layer and a Ta layer alternately stacked on a substrate, wherein the Cu layer is in contact with the substrate, and the Ta layer is the outermost layer. 2+The layer-by-layer release slows down its release rate, reduces cytotoxicity and obtains a lasting antibacterial effect; at the same time, the introduction of Ta effectively enhances the osteogenic properties of the matrix and promotes the proliferation of osteoblasts. The antibacterial coating of the present invention does not show cytotoxicity to rat bone marrow mesenchymal stem cells, can inhibit the growth of Staphylococcus aureus for a long time, and helps promote the proliferation of osteoblasts, and can be used as an antibacterial coating on the surface of bone implants.
[0022] The present invention also provides a method for preparing the antibacterial coating with TaCu nano multilayer structure described in the above technical solution. The preparation method of the present invention has the advantages of simple process, fast deposition speed and high bonding strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The cross-sectional morphology SEM images of the coatings of the groups Ta / Cu-1 (a), Ta / Cu-2 (b), Ta / Cu-3 (c), Ta / Cu-4 (d) and Ta / Cu-5 (e) obtained in Examples 1 to 5 when the deposition cycle is 20;
[0024] Figure 2 The relative proliferation rate diagram of the Ta / Cu-1, Ta / Cu-2, Ta / Cu-3, Ta / Cu-4, and Ta / Cu-5 coatings obtained in Examples 1 to 5 and rat bone marrow mesenchymal stem cells cultured for different time periods;
[0025] Figure 3 The enumeration results of Staphylococcus aureus by TC4 titanium alloy (a) and Ta / Cu-1 (b), Ta / Cu-2 (c), Ta / Cu-3 (d), Ta / Cu-4 (e), and Ta / Cu-5 (f) obtained in Examples 1 to 5;
[0026] Figure 4 The antibacterial rates of Ta / Cu-1, Ta / Cu-2, Ta / Cu-3, Ta / Cu-4 and Ta / Cu-5 groups obtained in Examples 1 to 5 against Staphylococcus aureus. DETAILED DESCRIPTION
[0027] The invention provides an antibacterial coating with a TaCu nano multilayer structure, comprising a Cu layer and a Ta layer which are alternately stacked on a substrate in sequence, wherein the Cu layer is in contact with the substrate and the Ta layer is the outermost layer.
[0028] The antibacterial coating with a TaCu nano multilayer structure provided by the present invention is arranged on a substrate, and the substrate is preferably a TC4 titanium alloy.
[0029] The antibacterial coating with a TaCu nano multilayer structure provided by the present invention comprises a Cu layer and a Ta layer alternately stacked on a substrate, the Cu layer is in contact with the substrate, and the Ta layer is the outermost layer. In the present invention, the single layer thickness of the Cu layer is independently preferably 2 to 3.5 nm. In the present invention, the single layer thickness of the Ta layer is independently preferably 11 to 12 nm. In the present invention, the number of layers of the Cu layer and the Ta layer is independently preferably ≥ 5 layers.
[0030] The present invention also provides a method for preparing the antibacterial coating having a TaCu nano multilayer structure as described in the above technical solution, comprising the following steps:
[0031] Pretreating the substrate to obtain a pretreated substrate;
[0032] The Cu layer and the Ta layer are alternately magnetron sputtered on the pretreated substrate in sequence to obtain the antibacterial coating with the TaCu nano multilayer structure.
[0033] In the present invention, unless otherwise specified, the raw materials used in the present invention are preferably commercially available products.
[0034] The present invention pretreats the substrate to obtain a pretreated substrate.
[0035] In the present invention, the material of the substrate is preferably consistent with the above technical solution, which will not be described in detail here.
[0036] In the present invention, the pretreatment preferably includes sequentially performing acetone ultrasonic washing and ethanol ultrasonic washing. In the present invention, the power of the acetone ultrasonic washing is preferably 90-100W, and the time is preferably 25-30min. In the present invention, the power of the ethanol ultrasonic washing is preferably 90-100W, and the time is preferably 25-30min.
[0037] After obtaining the pretreated substrate, the present invention sequentially and alternately magnetron sputters Cu layers and Ta layers on the pretreated substrate to obtain the antibacterial coating with the TaCu nano multilayer structure.
[0038] In the present invention, the parameters for alternately magnetron sputtering the Cu layer and the Ta layer on the pretreated substrate include: the protective atmosphere is preferably argon, the flow rate of the argon is preferably 30-35 sccm, the rotation speed of the substrate fixing table is preferably 3.8-5 r / s, the working gas pressure is preferably 0.5-0.75 Pa, the Cu target is preferably RF magnetron sputtering, the RF magnetron sputtering power is preferably 38-42 W, the Ta target is preferably DC magnetron sputtering, the DC magnetron sputtering power is preferably 98-102 W, the target-substrate distance is preferably 5-6 cm, and the alternating deposition of the Cu layer and the Ta layer is achieved by controlling the revolution position of the substrate fixing table. In the present invention, the single magnetron sputtering time ratio of the Cu target and the Ta target is preferably 1-5:10.
[0039] The antibacterial coating with TaCu nano multilayer structure and the preparation method thereof provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0040] The preparation, characterization and measuring instruments used in the examples are as follows:
[0041] The equipment used is a JGP-450 magnetron sputtering instrument produced by Shenyang Scientific Instrument Company.
[0042] The phase composition of the coating was analyzed by D8ADVANCE X-ray diffractometer produced by Bruker, Germany. The microscopic morphology of the coating was analyzed by Gemini 300 scanning electron microscope produced by ZEISS, Germany. The surface roughness of the coating was analyzed by Dimension Icon atomic force microscope produced by Bruker, Germany. The wetting properties of the coating were measured by JC2000C1 interfacial tension meter produced by Shanghai Zhongchen Digital Technology Equipment Co., Ltd. The Cu 2+ The release amount was measured; the CCK-8 method was used to detect the cytotoxicity of the coating, and the absorbance values of the experimental groups were analyzed by univariate analysis using SPSS22.0 software. P<0.05 indicated that the difference was statistically significant.
[0043] The antibacterial properties of the coatings were evaluated using the plate coating counting method.
[0044] Example 1
[0045] A method for preparing an antibacterial coating with a TaCu nano multilayer structure is to use a magnetron sputtering apparatus to alternately deposit two target materials, Cu and Ta, and the substrate is a TC4 titanium alloy. The preparation process includes the following steps:
[0046] (1) First, place the substrate in a beaker containing 100 mL of acetone and use ultrasonic cleaning for 30 minutes with the power set to 90 W; then place the substrate in a beaker containing 100 mL of anhydrous ethanol and use ultrasonic cleaning for 30 minutes with the power set to 90 W.
[0047] (2) A Cu layer and a Ta layer were sequentially deposited on a TC4 titanium alloy substrate by magnetron sputtering to obtain a Ta / Cu nano-multilayer antibacterial coating. The target materials used were pure Cu target and pure Ta target, with a diameter of 75 mm and a thickness of 3 mm. The Ar gas flow rate was 30 sccm. The DC magnetron sputtering power of the Ta target was 100 W. The RF magnetron sputtering power of the Cu target was 40 W. The deposition time ratio Ta:Cu was 10 s:1 s. The deposition cycle T was 5. The working gas pressure was 0.5 Pa. The target-substrate distance was 5 cm. The rotation speed of the substrate fixing disk was controlled to be 3.8 r / s. The antibacterial coating with a TaCu nano-multilayer structure was recorded as the Ta / Cu-1 group (the thickness of the single Ta layer was 11.5 nm, and the thickness of the single Cu layer was 2 nm).
[0048] Example 2
[0049] A method for preparing an antibacterial coating with a TaCu nano multilayer structure, wherein in step (2) of the preparation process, the deposition time ratio Ta:Cu=10s:2s, the deposition cycle T=5, and the antibacterial coating with a TaCu nano multilayer structure is recorded as a Ta / Cu-2 group (the thickness of a single Ta layer is 11.5nm, and the thickness of a single Cu layer is 2.5nm).
[0050] The rest is the same as in Example 1.
[0051] Example 3
[0052] A method for preparing an antibacterial coating with a TaCu nano multilayer structure, wherein in step (2) of the preparation process, the deposition time ratio Ta:Cu=10s:3s, the deposition cycle T=5, and the antibacterial coating with a TaCu nano multilayer structure is recorded as a Ta / Cu-3 group (the thickness of a single Ta layer is 11.5nm, and the thickness of a single Cu layer is 2.8nm).
[0053] The rest is the same as in Example 1.
[0054] Example 4
[0055] A method for preparing an antibacterial coating with a TaCu nano multilayer structure, wherein in step (2) of the preparation process, the deposition time ratio Ta:Cu=10s:4s, the deposition cycle T=5, and the antibacterial coating with a TaCu nano multilayer structure is recorded as a Ta / Cu-4 group (the thickness of a single Ta layer is 11.5nm, and the thickness of a single Cu layer is 2.9nm).
[0056] The rest is the same as in Example 1.
[0057] Example 5
[0058] A method for preparing an antibacterial coating with a TaCu nano multilayer structure, wherein in step (2) of the preparation process, the deposition time ratio Ta:Cu=10s:5s, the deposition cycle T=5, and the antibacterial coating with a TaCu nano multilayer structure is recorded as a Ta / Cu-5 group (the thickness of a single Ta layer is 11.5nm, and the thickness of a single Cu layer is 3.2nm).
[0059] The rest is the same as in Example 1.
[0060] In order to observe the clear structure of the coating cross section, the coating with deposition period T = 20 was used for observation. The results are shown in Figure 1 As shown, Figure 1 The cross-sectional morphology SEM images of the coatings of Ta / Cu-1, Ta / Cu-2, Ta / Cu-3, Ta / Cu-4 and Ta / Cu-5 obtained in Examples 1 to 5 when the deposition cycle is 20 are shown in FIG. Figure 1 It can be seen that the layered structure of the coating is clear and uniform, and the layers are superimposed to form a nano-multilayer structure coating; it can be obtained that when the deposition cycle T=5, the total thickness of the coating is 67.8nm, 70.6nm, 71.5nm, 71.9nm, and 73.4nm respectively.
[0061] The cytotoxicity of the coatings of Ta / Cu-1, Ta / Cu-2, Ta / Cu-3, Ta / Cu-4 and Ta / Cu-5 obtained in Examples 1 to 5 was measured respectively. Figure 2 Figure 1 is a graph showing the relative proliferation rates of the Ta / Cu-1, Ta / Cu-2, Ta / Cu-3, Ta / Cu-4 and Ta / Cu-5 groups of coatings obtained in Examples 1 to 5 and rat bone marrow mesenchymal stem cells cultured at different times. Table 1 is a graph showing the relative viability of the cells of each group of rat bone marrow mesenchymal stem cells cultured at different times.
[0062] Table 1 RGR and cytotoxicity levels of rBMSCs in each group at different culture times
[0063]
[0064]
[0065] As shown in Table 1, at 24h, the relative viability of the cells in the Ta / Cu-3, Ta / Cu-4, and Ta / Cu-5 groups of coatings was greater than 75%, and the toxicity level was Level I. At 72h and 120h, the relative viability of the cells was greater than 100%, and the toxicity level was Level 0, showing no obvious cytotoxicity, which helped to promote cell growth and met the standards for biosafety materials.
[0066] The antibacterial properties of the TC4 titanium alloy (a) and the Ta / Cu-1 (b), Ta / Cu-2 (c), Ta / Cu-3 (d), Ta / Cu-4 (e), and Ta / Cu-5 (f) coatings obtained in Examples 1 to 5 against Staphylococcus aureus were measured. The results are as follows: Figure 3 shown. Figure 3 The enumeration results of Staphylococcus aureus by TC4 titanium alloy (a) and Ta / Cu-1 (b), Ta / Cu-2 (c), Ta / Cu-3 (d), Ta / Cu-4 (e), and Ta / Cu-5 (f) obtained in Examples 1 to 5 are shown in FIG. Figure 4 The antibacterial rates of Ta / Cu-1, Ta / Cu-2, Ta / Cu-3, Ta / Cu-4 and Ta / Cu-5 obtained in Examples 1 to 5 against Staphylococcus aureus are shown in Table 1. Figure 3 From (a), we can see that bacteria survive well on the surface of the TC4 titanium alloy sample. After dilution, they are coated on the plate and multiply on the surface of the culture medium. A large number of colonies appear on the surface of the culture medium, indicating that the surface of the TC4 titanium alloy has no bactericidal effect; the corresponding coatings (b, c, d, e and f) have significantly fewer colonies in the culture medium. Figure 4 It can be seen that, taking the bacterial survival rate of the control group TC4 titanium alloy group as 100% as the standard, the antibacterial rates of the sample surfaces of the Ta / Cu-1, Ta / Cu-2, Ta / Cu-3, Ta / Cu-4, and Ta / Cu-5 groups were 70.38%, 95.49%, 90.97%, 67.09% and 99.63%, respectively, indicating that the antibacterial coating with TaCu nano multilayer structure with different deposition cycles formed by the addition of Cu element has different effects on the antibacterial properties of Staphylococcus aureus, among which the Ta / Cu-5 group has the highest antibacterial rate against Staphylococcus aureus, reaching 99.63%.
[0067] The coatings of Ta / Cu-1, Ta / Cu-2, Ta / Cu-3, Ta / Cu-4 and Ta / Cu-5 obtained in Examples 1 to 5 were subjected to Cu 2+ The release rate of Cu 2+ It can be released stably for 7 days. As the Cu content increases, Cu 2+ The release amount of Cu in the Ta / Cu-5 group also gradually increased. 2+ The total amount released is the highest.
[0068] In summary, the present invention obtains an antibacterial coating with a TaCu nano multilayer structure by magnetron sputtering technology, and controls the content of Cu element in the coating by controlling the size of the deposition time ratio, and finally obtains an antibacterial coating with a TaCu nano multilayer structure obtained by magnetron sputtering technology. The obtained coating has a cytotoxicity of level 0, meets the safety standards of biomaterials, has excellent antibacterial properties and has osteogenic activity.
[0069] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An antibacterial coating having a TaCu nano multilayer structure, characterized in that: The invention comprises a Cu layer and a Ta layer which are alternately stacked in sequence on a substrate, wherein the Cu layer is in contact with the substrate, and the Ta layer is the outermost layer.
2. The antibacterial coating according to claim 1, characterized in that: The number of the Cu layer and the Ta layer is independently ≥5 layers.
3. The method for preparing the antibacterial coating having a TaCu nano multilayer structure according to any one of claims 1 to 2, characterized in that: The following steps are involved: Pretreating the substrate to obtain a pretreated substrate; The Cu layer and the Ta layer are alternately magnetron sputtered on the pretreated substrate in sequence to obtain the antibacterial coating with the TaCu nano multilayer structure.
4. The preparation method according to claim 3, characterized in that: Parameters for alternately magnetron sputtering the Cu layer and the Ta layer on the pretreated substrate include: the protective atmosphere is argon, the working gas pressure is 0.5-0.75 Pa, the Cu target is RF magnetron sputtering, the RF magnetron sputtering power is 38-42 W, the Ta target is DC magnetron sputtering, the DC magnetron sputtering power is 98-102 W, and the alternating deposition of the Cu layer and the Ta layer is achieved by controlling the revolution position of the substrate fixing table.
5. The preparation method according to claim 4, characterized in that: The single magnetron sputtering time ratio of the Cu target to the Ta target is 1 to 5:
10.
6. The preparation method according to claim 4, characterized in that: The parameters for alternately magnetron sputtering the Cu layer and the Ta layer on the pretreated substrate further include: the rotation speed of the substrate fixing table is 3.8-5 r / s.
7. The preparation method according to claim 4, characterized in that: The parameters for alternately magnetron sputtering the Cu layer and the Ta layer on the pretreated substrate also include: the target-substrate distance is 5-6 cm.
8. The preparation method according to claim 4, characterized in that: The flow rate of the argon gas is 30-35 sccm.
9. The preparation method according to claim 3, characterized in that: The pretreatment comprises sequentially performing acetone ultrasonic washing and ethanol ultrasonic washing; The power of the acetone ultrasonic washing is 90-100W, and the time is 25-30min; The power of the ethanol ultrasonic washing is 90-100W, and the time is 25-30 minutes.
10. The preparation method according to claim 3, characterized in that: The substrate is TC4 titanium alloy.
Citation Information
Cited By
Biomedical multifunctional coating and preparation method thereof
CN119615094A
Method for improving bonding strength of tantalum coating on surface of biomedical peek material
CN119615095A
